2018
DOI: 10.1016/j.carbpol.2017.09.096
|View full text |Cite
|
Sign up to set email alerts
|

Gums induced microstructure stability in Ca(II)-alginate beads containing lactase analyzed by SAXS

Abstract: Previous works show that the addition of trehalose and gums in β-galactosidase (lactase) Ca(II)-alginate encapsulation systems improved its intrinsic stability against freezing and dehydration processes in the pristine state. However, there is no available information on the evolution in microstructure due to the constraints imposed by the operational conditions. The aim of this research is to study the time course of microstructural changes of Ca(II)-alginate matrices driven by the presence of trehalose, arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…Pectin is part of the beads structure forming the 3D hydrogel network with alginate. The microstructure of the alginate hydrogel network determined by small‐angle X‐ray scattering (SAXS) showed that both compactness and density of alginate rods are drastically affected by other biopolymers (Traffano‐Schiffo et al ., , ), affecting the 3D network as well as water distribution. It was reported that pectin also forms rod‐like objects like alginate, of smaller size but with much higher flexibility, showing the ability to form different networks architecture (Schuster et al ., ), which may protect lycopene by improving interactions between them.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pectin is part of the beads structure forming the 3D hydrogel network with alginate. The microstructure of the alginate hydrogel network determined by small‐angle X‐ray scattering (SAXS) showed that both compactness and density of alginate rods are drastically affected by other biopolymers (Traffano‐Schiffo et al ., , ), affecting the 3D network as well as water distribution. It was reported that pectin also forms rod‐like objects like alginate, of smaller size but with much higher flexibility, showing the ability to form different networks architecture (Schuster et al ., ), which may protect lycopene by improving interactions between them.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies of encapsulation of bioactive compounds such as flavours, drugs, enzymes, vitamins, essential oils and carotenoids in a matrix or core system have been developed to control their release and protect them from deteriorative processes like oxidation, evaporation, degradation or thermal denaturation (Ray et al ., ; Traffano‐Schiffo et al ., , ). In particular, the simple and mild aqueous‐based gel formation achieved by the ionotropic gelling of Ca(II)‐alginate remains a very attractive alternative for biomedical, food and pharmaceutical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the encapsulation of phenolic compounds in biopolymer matrices represents a great possibility in their incorporation and consumption in different food systems [ 13 ]. The effectiveness of Ca(II)-alginate hydrogels in the stabilization and controlled release of biomolecules has been widely demonstrated [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For AS preparation, a 1% (w/v) alginate with 20% (w/v) sucrose was dropped into the 2.5% (w/v) CaCl 2 solution supplemented with 20% (w/v) sucrose using the same procedure previously described. A peristaltic pump (Damova S.L., Barcelona, Spain, model CPM-045B) was used to Ca(II)-alginate bead production according to the drop method described by Traffano-Schiffo et al, (2017), with a pump speed at 20 ± 0 rpm, regulated by an inverter Panasonic DV-700 (Oasaka, Japan) [12] . The CaCl 2 solution (with or without sucrose) was maintained in a cold bath with constant stirring by using a vortex IKA ® MS3 basic (IKA, Staufen, Germany).…”
Section: Hydrogel Beads Preparationmentioning
confidence: 99%